Information acquisition and financial intermediation - Nina Boyarchenko (Federal Reserve Bank of New York, 2012)
This paper considers the problem of information acquisition in an intermediated market, where the specialists have access to superior technology for acquiring information. These informational advantages of specialists relative to households lead to disagreement between the two groups, changing the shape of the intermediation-constrained region of the economy and increasing the frequency of periods when the intermediation constraint binds. Acquiring the additional information is, however, costly to the specialists, making them less likely to decrease their risky asset holdings when the intermediation constraint binds. I show that this behavior leads the equity capital constraint to bind more frequently, making asset prices in the economy more volatile. I find empirical evidence consistent with these predictions.
Keywords: G12; G19; E44; G00; 330; rational inattention; asset prices in intermediated economies